2020
DOI: 10.33988/auvfd.677150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dried thyme (Thymus vulgaris L.) leaves on performance, some egg quality traits and immunity in laying hens

Abstract: The aim of the present study was to investigate the usage of thyme leaves and its effects on performance, some egg quality traits and humoral immunity in laying hens. A total of 108 laying hens aged 36 weeks were randomly assigned to three dietary groups for 16 weeks. Dried and ground (Thymus vulgaris L.) thyme leaves were used at the level of 0, 1 and 2% in the diets of groups. Feed intake, body weight, egg production, egg weight and egg quality characteristics were not affected by dietary thyme supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Vakili and Majidzadeh Heravi 17 also found that palmitic acid decreased and linolenic acid increased in egg yolk with thyme extract supplementation. The fatty acid composition of the egg yolk is closely related to the feed lipids consumed by the laying hens, and linoleic acid in yolk was increased significantly 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Vakili and Majidzadeh Heravi 17 also found that palmitic acid decreased and linolenic acid increased in egg yolk with thyme extract supplementation. The fatty acid composition of the egg yolk is closely related to the feed lipids consumed by the laying hens, and linoleic acid in yolk was increased significantly 18 .…”
Section: Resultsmentioning
confidence: 99%
“…EOs also increased the immunity and antioxidant capacity in heat stress periods (Eler et al, 2019;Sariözkan et al, 2020). In layer hen, along with improving growth performance characteristics, EOs improve egg quality and shell related parameters (Abo Ghanima et al, 2020;Yalçin et al, 2020). As documented in the literature, EOs exhibit antimicrobial activity against Escherichia coli (Park and Kim, 2018), Clostridium perfringens (Cho et al, 2014), Salmonella typhimurium (Ahmed et al, 2013), and prevent the adhesion, colonization, and proliferation in the gut of broiler.…”
Section: Effects Of Eos On the Digestive System Of Monogastric Animalsmentioning
confidence: 99%
“…In terms of ruminant nutrition, EOs enhance animal performance, manipulate rumen fermentation such as increase protein metabolism, reduce ammonia and methane production, improve volatile fatty acids (VFA) proportions and target some ruminal microorganisms like methane-producing archaea and hyper-ammonia producing (HAP) bacteria (Campolina et al, 2020;Hart et al, 2019;Silva et al, 2020;Tapki et al, 2020;Zhou et al, 2020). They also possess remarkable effects on monogastric animals like improve digestive secretions, body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), meat, and egg qualities (Ismail, El-Gogary, and El-Morsy, 2019;Masood et al, 2020;Sariözkan et al, 2020;Yalçin et al, 2020). They also exhibit antioxidant properties, stimulate blood circulation, reduce the pathogens count, enhance digestion and nutrient uptake, and relieve the animals from disease and environmental stress.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is no study available concerning the geometrical properties of eggs in chicken fed on thyme supplemented diet despite a large number of studies that investigated the effects of thyme supplementation on egg quality parameters (Bolukbasi and Erhan, 2007;Ghasemi et al, 2010;Abd El-Hack and Alagawany, 2015;Yalcin et al, 2020). Intrinsic and extrinsic egg quality parameters were evaluated in such studies.…”
Section: Research Articlementioning
confidence: 99%